Electronic structure and optical property of metal-doped Ga2O3: a first principles study. Issue 82 (17th August 2016) - Tang, Cheng; Sun, Jie; Lin, Na; Jia, Zhitai; Mu, Wenxiang; Tao, Xutang; Zhao, Xian
Abstract : A long list of main group and transition metals, even some lanthanides, have been examined based on first principles studies, to search for potential p-type dopants for β-Ga2 O3 . Abstract : The difficulty in fabricating p-type Ga2 O3 is a crucial issue which restricts its applications in practical devices. In the present work, we have performed first principles studies on formation energies, electronic structures and optical properties for a series of metal doped β-Ga2 O3, involving a long list of main group and transition metals, even some lanthanides, to search for potential p-type dopants. Calculations have shown that Li and Be, both with small atomic radius, prefer interstitial doping rather than substitutional doping of Ga, resulting eventually in an n-type character to the doped system. In addition, an O-rich atmosphere is more favorable for p-type substitutional dopings by comparison with the Ga-rich condition. A number of metal dopants show potential in achieving p-type β-Ga2 O3, for example, Na, Mg, Ca, Cu, Ag, Zn, Cd, which are all worth a further emphasis study in experiment, although a satisfying holes concentration may only be possible to achieve by simultaneously committing to both the elimination of n-type background carriers and the activation mechanism of dopants. Absorption spectra have shown that all the above-mentioned potential p-type dopants are suitable for deep UV applications. The major peaks of the absorption spectra are red-shifted in most cases, due to the introduction of new states to the forbidden gap by dopants, which have been discussed in detail by inspecting into the partial density of states. Ga2 O3 doped by some transition metals show potential as magnetic devices.